2012
DOI: 10.1007/s13127-012-0110-6
|View full text |Cite
|
Sign up to set email alerts
|

Insights into panicoid inflorescence evolution

Abstract: Your article is protected by copyright and all rights are held exclusively by Gesellschaft für Biologische Systematik. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Management of grassy ecosystems requires understanding of grass biology that includes their breeding systems. Grasses display a broad spectrum of breeding systems, inflorescence types and physiology (Campbell et al 1983;Quiroga et al 2010;Christin et al 2012;Reinheimer et al 2013aReinheimer et al , 2013b. Breeding systems in grasses include asexual reproduction, both vegetative and by seeds (apomixis), and types of pollination ranging from outcrossing with self-incompatibility to self-compatible (Connor 1979;Richards 1990;Gibson 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of grassy ecosystems requires understanding of grass biology that includes their breeding systems. Grasses display a broad spectrum of breeding systems, inflorescence types and physiology (Campbell et al 1983;Quiroga et al 2010;Christin et al 2012;Reinheimer et al 2013aReinheimer et al , 2013b. Breeding systems in grasses include asexual reproduction, both vegetative and by seeds (apomixis), and types of pollination ranging from outcrossing with self-incompatibility to self-compatible (Connor 1979;Richards 1990;Gibson 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Self-pollination is viewed as an evolutionary adaptation to environmental influences (Lord 1981;Lloyd and Schoen 1992;Quiroga et al 2010;Sicard and Lenhard 2011;Reinheimer et al 2013aReinheimer et al , 2013b. Furthermore, the presence, abundance and, in some cases, the nature of the expression of CL, are affected by ecological, morphological and physiological factors (Lindauer and Quinn 1972;Clay 1982;Campbell et al 1983;Clay and Antonovics 1985;Philipson 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Only the general terms raceme, spike and panicle have been used to describe its diversity (De Wet and Harlan, 1970;Hilu and Alice, 2001;Liu et al, 2005;Neves et al, 2005;Jewell et al, 2012b;Snow et al, 2013;Kellogg, 2015a;Peterson et al, 2015); nevertheless, this assumption is based on general descriptions of a small number of species. Previous studies have demonstrated that a better understanding of the diversity of inflorescence types can be achieved when morphological data are analyzed in a comparative manner based on phylogeny (Liu et al, 2005;Reinheimer et al, 2013;Pilatti, 2016). In addition, even with the possibility of finding more types than initially assumed for a group, it has been shown that the frequency of occurrence of the types may vary, where some types are more frequently observed than others (Reinheimer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that a better understanding of the diversity of inflorescence types can be achieved when morphological data are analyzed in a comparative manner based on phylogeny (Liu et al, 2005;Reinheimer et al, 2013;Pilatti, 2016). In addition, even with the possibility of finding more types than initially assumed for a group, it has been shown that the frequency of occurrence of the types may vary, where some types are more frequently observed than others (Reinheimer et al, 2013). These observations uncover the existence of constraints (genetic, developmental, or environmental) that direct the evolution of the inflorescence.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it was previously assumed that the paired spikelet trait found in some species of the Paniceae, Paspaleae, and Andropogoneae tribes could have arisen independently several times, or arisen in the common ancestor of the three tribes but was subsequently lost (i.e., reversion to single spikelets; Figure 3-1). Additionally, the Andropogoneae tribe was classified as the only grass tribe composed exclusively of paired spikelet species (Tanaka et al 2013;Reinheimer et al 2013).…”
Section: Discussionmentioning
confidence: 99%